Learning Algebra through Mathmagic and Geometry by using Animations: Belajar Aljabar melalui Mathmagic dan Geometri menggunakan Animasi - Irvandi Gorby Pasangka; Jusrry Rosalina Pahnael; Ganesha Lapenangga Putra; Yoseph Sugi (Yayasan Ahmar Cendekia Indonesia, 2020)
Mathematics is a basic science that need to be learned at the levels of elementary school, middle school and high school and even at the tertiary level. However, there are still many students who have difficulty in learning mathematics, this is evidenced by their low test scores, one of which is the mathematics test scores. Regarding to these problems, an activity was carried out with the aim of assisting students in understanding mathematics, specifically algebraic and geometric materials for junior high school students, by providing material as attractive as possible so that students become interested and motivated in learning mathematics. The provision of material was carried out in 3 sessions, namely: 1) Delivering algebraic material through mathmagic, 2) Delivering geometric material through animation, 3) Providing motivation about the importance of learning mathematics. Based on the results of this implementation, it can be found that the participants are able to understand and enjoy the learning process with the material presented by the teacher, this can be seen from the activities of the participants during the activity. Abstrak Matematika merupakan ilmu dasar yang wajib kita pelajari di tingkat SD, SMP, SMA bahkan perguruan tinggi, namun pada kenyataannya, siswa-siswi masih sulit dalam mempelajari matematika, ini dibuktikan dari rendahnya nilai ujian mereka, salah satunya nilai ujian nasional matematika. Berdasarkan masalah ini, kegiatan ini ditujukan untuk membantu siswa-siswi dalam memahami matematika khususnya materi aljabar dan geometri untuk siswa-siswi SMP, yaitu dengan cara memberikan materi semenarik mungkin sehingga para siswa menjadi suka dan termotivasi dalam belajar matematika. Pemberian materi dilakukan dalam 3 sesi yaitu: 1) Pemberian materi aljabar melalui mathmagic, 2) Pemberian materi geometri melalui animasi, 3) Pemberian motivasi tentang pentingnya belajar matematika. Berdasarkan hasil pelaksanaan yang dilakukan, dapat diketahui bahwa para peserta dapat menangkap dan menikmati proses pemberian materi yang diberikan, hal ini terlihat dari keaktifan para peserta selama kegiatan.